Maize hybrids’ genetic variability based on qualitative and quantitative traits - Priyanto, Slamet Bambang; Herawati, Herawati; Suwarti, Suwarti; Rahman, Ayyub Ar; Andayani, Nining Nurini; Fattah, Abdul; Azrai, Muhammad (Kultivasi, 2024)
Genetic variability was a prerequisite to doing a plant breeding program. A broad genetic variability allows plant breeders to select a desired genotype. This research aims to assess the maize hybrid's genetic variability based on qualitative and quantitative traits. This research was conducted in the Bone district, south Sulawesi, from November 2022 to March 2023. Fifteen maize hybrids were arranged in a randomized complete block design with three replications. The variables observed are qualitative and quantitative traits. Principal component (PCA) and cluster analyses assessed the genetic variability. The result indicated that based on a loading factor greater than 0.70, the qualitative traits such as intensity of green color, anthocyanin coloration of brace roots, length of lateral branch, intensity anthocyanin coloration of silk, and degree of zigzag displayed high variability. quantitative like days to anthesis, days to silk, leaf length, 1000 seeds weight, yield, ear diameter, number of row seeds per ear, ear height, ear length, and number of seeds per row also exhibit high variability. Cluster analysis shows a broad genetic variability on qualitative and quantitative traits demonstrated by Euclidean levels 6.68-10.93 and 3.43-5.08, respectively, and generated the dendrogram that divides genotypes into four main clusters for qualitative and five for quantitative traits.